IMPLEMENTASI ALGORITMA KRIPTOGRAFI RC4 DAN METODE STEGANOGRAFI AUDIO 2LSB PADA SISTEM KEAMANAN INFORMASI - Ely Setyo Astuti; Binar Prihadmantyo; Meyti Eka Apriyani (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2019)
Providing security and confidentiality to information is needed when exchanging information through communication networks. It is intended that the information sent by the sender can be received in full by the recipient without any interference from parties who are not interested in the information.Cryptographic techniques and steganography can be used to secure confidential messages. Building applications that combine these two techniques can provide security for confidential messages well. Security techniques that can be used are cryptographic techniques using the RC4 algorithm to secure secret messages in the form of text or images, and insert secret messages with 2LSB steganography method into audio media.The analysis carried out is the level of success of the message insertion and extraction process, process speed, stego audio attack, and audio quality. The results of 18 times insertion testing and message extraction, obtained a success percentage of 100% with different processing times depending on the size of the message being inserted. The resulting Stego audio has good quality and does not cause noise that can be heard directly by the human senses, but stego audio cannot withstand attacks that cause changes to the stego file byte value. So it can be concluded that the combination of the RC4 cryptographic algorithm and the 2LSB steganography method can secure the message properly and provide the results of decryption without any changes to the inserted message